Arduino Cookbook Recipes to Begin, Expand, and Enhance Your Projects - Margolis, Michael; Jepson, Brian; Weldin, Nicholas Robert (O'Reilly Media, 2020)
Want to create devices that interact with the physical world? This cookbook is perfect for anyone who wants to experiment with the popular Arduino microcontroller and programming environment. You'll find more than 200 tips and techniques for building a variety of objects and prototypes such as IoT solutions, environmental monitors, location and position-aware systems, and products that can respond to touch, sound, heat, and light. Updated for the Arduino 1.8 release, the recipes in this third edition include practical examples and guidance to help you begin, expand, and enhance your projects right away-whether you're an engineer, designer, artist, student, or hobbyist.